UMPSA Prihatin Tour cares for students’ needs ahead of registration - Naqiah, Puaad (UMPSA, 2025)
KUALA LUMPUR, 18 September 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) reached out to new students in need as an initiative and to facilitate their registration process on 27 September.